Selection and Identification of Cellulase-Producing Bacteria Isolated from the Litter of Mountain and Swampy Forest - . WIZNA; HAFIL ABBAS; YOSE RIZAL; ABDI DHARMA; I PUTU KOMPIANG (Indonesian Society for microbiology, 2007)
The isolation and selection of cellulase-producing bacteria was conducted to identify the species of cellulolytic Bacillus. The bacteria were isolated from the litter of swampy forest in Pesisir Selatan and mountain forest in Lembah Anai Tanah Datar. These bacteria were cultivated in selective media to obtain bacteria from the genus Bacillus. Six Bacillus isolates were obtainedfrom swampy forest and three Bacillus isolates from mountain forest. These isolates were cultivated in agar medium with carboxymethylcellulose as the carbon source. Colonies which produced clear zones were assumed to be cellulolytic Bacillus. Based on biochemical and morphological examinations the result indicated that these two isolates were Bacillus coagulans and B. amyloliquefaciens. The cellulase activity of B. coagulans and B. amyloliquefaciens were 0.812 and 1 200 unit ml-1 to C1(b-exoglucanase) respectively, 0.368 and 0.488 unit ml-1 to Cx(b-endoglucanase) respectively.